กลยุทธ์การบริหารโรงเรียนเอกชนระดับมัธยมศึกษาตามแนวคิดการพัฒนานักเรียนให้มีภาวะผู้นำอย่างคล่องแคล่ว - ปาฑ์ ไกรวิญญ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The research objectives were to 1) study the conceptual framework of private secondary school management and students’ agile leadership development 2) study the current and the desirable states of private secondary school management according to the concept of developing the students’ agile leadership and 3) develop private secondary school management strategies according to the concept of developing the students’ agile leadership. The research applied an explanatory sequential mixed methods design through quantitative data collection and qualitative data collection. The samples were 240 private secondary schools in Thailand. The research instruments were questionnaires and strategic evaluation form to testify feasibility and appropriateness of the strategies. The quantitative data were analyzed by percentage, frequency, mean, standard deviation, PNImodified and qualitative data were analysed by content analysis.The results were as follows: 1. the conceptual framework of private secondary school management consisted of school curriculum development, teaching and learning learner development activities ,and assessment and evaluation. 2. the conceptual framework of developing the students’ agile leadership will develop students in the following areas 1) Situational Awareness 2) Sense of Purpose 3) Stakeholder Understanding 4) Power Style 5) Connective Awareness 6) Reflective Judgement 7) Self-awareness 8) Developmental Motivation 2. The current state of private secondary school management strategies according to the concept of developing the students’ agile leadership as a whole was at the high level ( x̄ = 3.5735) while the desirable state as a whole was at the highest level ( x̄ = 4.5777). 3. Private secondary school management strategies according to the concept of developing the students’ agile leadership consisted of 3 main strategies: 1) Increase the effectiveness of assessment and evaluation management to develop student’ agile leadership with 2 sub strategies and 10 procedures. 2) Enhance the instructional management to develop student’ agile leadership with 2 sub strategies and 10 procedures. 3) Modify school curriculum to develop student’ agile leadership with 2 sub strategies and 8 procedures.